(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
With the end of the Second World War and the process of decolonization in international politics under the aegis of the United Nations, many new nations emerged in Asia, Africa and Latin American countries. India was one of the nations that emerged as independent nation a result of the decolonization process. With the status of an independent nation, a new challenged that was posed before the Indian nation was the administration of India as one country, the integration of all princely states and the process of nation building through the existence of a constitution and a strong administrative machinery. The challenged was addressed through the framing of the Indian Constitution and the adoption of the federal form of government. Whereas, the Constitution was deemed to deliver rule of law and democracy, the federal nature was meant to address the aspirations and particular identity of the federating units. Hence, after Indian independence, the nation’s administrative machinery operates as perceived and desired by the nation builders and founding fathers of the nation. There was cordial relationship between the Centre and the States during 1947 – 1967. The period was an era of one party dominance in which the Indian National Congress was ruling with absolute majority, both at the Centre and in the States.